Strategies to Circumvent the Side-Effects of Immunotherapy Using Allogeneic CAR-T Cells and Boost Its Efficacy: Results of Recent Clinical Trials - Smirnov, Sergei; Petukhov, Alexey; Levchuk, Ksenia; Kulemzin, Sergey; Staliarova, Alena; Lepik, Kirill; Shuvalov, Oleg; Zaritskey, Andrey; Daks, Alexandra; Fedorova, Olga (Frontiers in Immunology, 2021)
Despite outstanding results of autologous CAR-T cells treatment in hematological malignancies, this approach is endowed with several constraints. Particularly, profound lymphopenia in some patients and the inability to produce products with predefined properties or cells with multiple modifications in advance. Allogeneic CAR-T cells bear the potential to address these issues but could cause life-threatening GVHD or have shorter persistence period due to elimination by the host immune system. Currently, novel strategies to create the ‘of the shelf’ allogeneic product that would circumvent these limitations comprise an extensive area of nowadays research. Here we review CAR-T cell products pioneering an allogeneic approach in clinical trials.